Effects of Competition on The Crown Width Allometry for Dominant Trees on Good Sites of Vegetative Clonal Teak (Tectona grandis Linn. f.) in Java, Indonesia - Sadono, Ronggo (Jurnal Manajemen Hutan Tropika, 2019)
The vegetative clonal teak is fast-growing, exhibits relatively uniform growth, and is sensitive to crown competition. The crown width dimension correlates positively with the size of the diameter (CW allometry). We investigated the effects of competition on CW allometry for dominant trees on good sites and the prediction accuracy of CW allometry. The data were measured during 2015–2017. The Hegyi index with a fixed 30° search cone method was used to measure competition. The scatter plot of all observations was used to identify the general pattern of CW over diameter, and competition index with both diameter and CW. The data were classified into three groups, ignored, free, and occurred competition data sets. Moreover, the occurred competition data set was categorized into three levels: low, medium, and heavy. The power model was used for parameterization of CW allometry. The dispersion of CW over diameter for all observations exhibited a moderate positive correlation, as well as the competition index with both diameter and CW. For the ignored-competition data set, the CW allometry was able to describe approximately 37.2% of observed CW. Interestingly, however, the prediction accuracy increased to 44.6% for the free competition data set. In contrast, the capability of the CW allometry for the occurred competition data set declined sharply to 9.1%. Among the occurred competition data sets, the heavier the subject trees competed, the lower the CW allometry explained the variations. However, the CW allometry was completely not able to describe the observed CW in the heavy competition level.